2015
DOI: 10.1002/cbic.201500042
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Protein Labeling by Using Lipoic Acid Ligase with Norbornene Substrates and Subsequent Inverse‐Electron Demand Diels–Alder Reaction

Abstract: Inverse-electron-demand Diels-Alder cycloaddition (DAinv ) between strained alkenes and tetrazines is a highly bio-orthogonal reaction that has been applied in the specific labeling of biomolecules. In this work we present a two-step labeling protocol for the site-specific labeling of proteins based on attachment of a highly stable norbornene derivative to a specific peptide sequence by using a mutant of the enzyme lipoic acid ligase A (LplA(W37V) ), followed by the covalent attachment of tetrazine-modified fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…83 Similarly, by using LplA W37V, Wombacher et al successfully ligated a norbornene derivative with a transmembrane protein with an extracellular LAP-tag in HEK293T cells. 169 4.2.3 Protein farnesyltransferase. Protein farnesyltransferase (PFTase) has been used to covalently attach farnesyl diphosphate site-specifically at the cysteine residue of the recognizing sequence CAAX (Fig.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…83 Similarly, by using LplA W37V, Wombacher et al successfully ligated a norbornene derivative with a transmembrane protein with an extracellular LAP-tag in HEK293T cells. 169 4.2.3 Protein farnesyltransferase. Protein farnesyltransferase (PFTase) has been used to covalently attach farnesyl diphosphate site-specifically at the cysteine residue of the recognizing sequence CAAX (Fig.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…25,26 LplA specifically recognizes the LAP-tag, which consists of 22 aa, and accepts different lipoic acid derivatives containing alkyne, azide, trans-cyclooctene, aryl aldehyde or aryl hydrazine groups as well as fluorophores. 25,[27][28][29] Strain-promoted alkyne-azide cycloaddition (SPAAC), hydrazone formation or Diels-Alder cycloaddition 30 enabled the subsequent chemical modification of the lipoic acid appendage on LAP-tagged proteins such as CFP, 25 BFP, 28 low-density lipoprotein receptor (LDLR), 25 neurexin-1b 27 or actin. 28 The LplA mutant LplA W37V has been reported to provide higher ligation yields than the wild-type enzyme.…”
Section: Reported Tag Positionsmentioning
confidence: 99%
“…32 Wombacher et al reported norbornene-conjugated lipoic acid analogues, which were introduced into LAP-tagged CFP and dihydrofolate reductase from E. coli (eDHFR) and fluorescently labelled via inverse-electron demand Diels-Alder reaction. 30 The enzyme tubulin tyrosine ligase (TTL) allows the C-terminal labelling of proteins with a 14 aa hydrophilic recognition sequence called Tub-tag. TTL is a regulator of microtubule homeostasis and usually promotes the coupling of tyrosine to the a-tubulin C-terminus.…”
Section: Reported Tag Positionsmentioning
confidence: 99%
“…Other variants of trans ‐cyclooctene have also been tested, but compound 57 is the most effectively ligated. Other research groups have made use of norbornene instead of trans ‐cyclooctene as the iEDDA partner . LplA is able to recognize a LplA acceptor peptide (LAP) and site‐selectively tag the protein of interest.…”
Section: Applications Of Iedda Reactionsmentioning
confidence: 99%